THE EFFECT OF INQUIRY BASED LEARNING WITH SOCIOSCIENTIFIC ISSUES CONTEXT ON CRITICAL THINKING SKILLS AND SCIENTIFIC EXPLANATION - Intan Mahanani; Sri Rahayu; Fauziatul Fajaroh (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran)
This study was aimed at investigating the application of inquiry learning in the context of socioscientific issues (SSI) influences students' skills in critical thinking and scientific explanation on the topic of reaction rates. This study was quantitative research used post test only control group design. A total of 90 students who were enrolled in the 3 classes from one public senior high school in Malang regency were selected as the research sample by convenience. The data of critical thinking ability were collected through critical thinking test. The data of scientific explanation were collected through scientific explanation test. The results of critical thinking test were categorized by Ennis’s critical thinking, while the results of scientific explanation test were categorized by SOLO taxonomy. The data were analysed quantitatively by statistical parametric. The result of One-Way ANOVA showed that there were significant differences in students' critical thinking skills and scientific explanation ability who were taught by inquiry with SSI learning, inquiry, and verification model. Students who were taught by inquiry with SSI learning had a higher average of critical thinking and scientific explanation skills than the students who were taught by inquiry and verification learning. PENGARUH PEMBELAJARAN INKUIRI BERKONTEKS SOCIOSCIENTIFIC-ISSUES TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN SCIENTIFIC EXPLANATION